Financial System Architecture and the Patterns of International Trade - Emmanuel Amissah; Spiros Bougheas; Fabrice Defever; Rod Falvey (Center for Economic Studies and ifo Institute (CESifo), 2016)
Countries differ on the extent to which their financial system relies on banks or on the financial market. We offer a model featuring a possible two way relationship between countries' financial system architecture and their comparative advantage. Countries specialising in bank dependent sectors favour the development of the banking sector. Simultaneously, countries with more efficient capital markets develop comparative advantage in sectors with strong dependence on market finance. To empirically investigate our model's predictions, we construct a measure of sector bank dependence and establish a strong relationship between countries' comparative advantage and their financial system architecture.
Keywords: F10; G20; G21; 330; financial systems; trade patterns; banks; direct finance